Perancangan User Interface pada Aplikasi ‘LiteraLink’ dengan Menggunakan Metode Design Thinking - Sare, Lusia Elvira Sue; Suhartana, I Ketut Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 3 No 2 (2025): JNATIA Vol. 3, No. 2, Februari 2025DO - 10.24843/JNATIA.2025.v03.i02.p17, 2025)
The level of reading interest among Indonesian people will be 66.7 points in 2023. Increasingly advanced technological developments have led to an increase in the use of digital media, including reading practices which now tend to be digital. Previous research has involved the use of design thinking in creating solutions from a process of empathy for a particular human-centered need. So the design thinking method was used in designing the "LiteraLink" application. Before starting a series of steps in design thinking, it is important to first determine the target user in accordance with the objectives of this application. The results of the interface design test using SUS are shown in Table 2 and produced a score of 80 16. Based on the SUS assessment indicators, the score is categorized as grade B or excellent so that the results of this interface design are acceptable. Based on the results of the research that has been carried out, it can be concluded that the application of the design thinking method in designing the interface of the digital reading application in the 'LiteraLink' application is successful  implemented so that this application is considered good and has the potential to increase interest in reading and support literacy among the community, especially children and teenagers.